ANTIMICROBIAL PROPERTIES OF A ZULU HERBAL MIXTURE ’IMBIZA EPHUZWATO’ - Ndhlala, A.; Stafford, G.; Finnie, J.; Van Standen, J. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Imbiza ephuzwato is a Zulu herbal preparation consisting of roots, bulbs, rhizomes and leaves of several medicinal plants extracted with boiling water. The herbal mixture, sold in muthi shops around KwaZulu-Natal is used to treat microbial and fungal infections, boost energy and relieve general body pains. Imbiza ephuzwato was tested against two Gram-positive (Bacillus subtilis and Staphylococcus aureus), two Gram-negative (Escherichia coli and Klebsiella pneumoniae) bacteria and Candida albicans using the microdilution assay to evaluate its antimicrobial effects. The mixture showed antibacterial and antifungal activity with a minimum inhibitory concentration (MIC) of 0.78 mg/ml against the microbes tested. Six of the plant constituents (Corchorus aspleniifolius root, Cyrtanthus obliquus bulb, Drimia robusta bulb, Gunnera perpensa rhizome, Hypericum aethiopicum leaf and Zanthoxylum capense root) of Imbiza ehuzwato were extracted with petroleum ether, 80% ethanol and water. The extracts were subjected to similar tests to investigate the source of activity of the mixture. The aqueous extracts of G. perpensa rhizome showed MIC values of 0.78 mg/ml against the bacteria and fungus. The petroleum ether extract of C. aspleniifolius root showed MIC values of 0.195 mg/ml against all the bacteria and 0.39 mg/ml against C. albicans. The rest of the plants had MIC values ranging from 0.39 to 12.5 mg/ml against both the bacteria and fungus used. The results suggest G. perpensa rhizome could be the source of the activity detected in the product. G. perpensa rhizome contains several compounds with antibacterial activity. Isolation of active components will be attempted from the other active extracts.